Bridging Theory and Practice: A Systematic Review of Educational Philosophy in Digital Learning Contexts - Devi Sylvianica; Dewi Angraini; Yeni Susanti; Meli Irzaleny; Netti Herawati (Journal of Social Work and Science Education, 2026)
The integration of digital technology into education presents both transformational opportunities and complex challenges for today's learning systems. This research aims to bridge classical educational philosophy theories—particularly pragmatism, constructivism, and humanism with the realities of digital learning. Using the Systematic Literature Review (SLR) method, this research synthesizes findings from scientific articles published between 2020 and 2025 to analyze the application of philosophical principles in technology-based pedagogical practices. The results show that educational philosophy continues to play a crucial role in shaping meaningful digital learning by fostering critical thinking, creativity, independent learning, and ethical awareness. However, issues such as the digital divide, shallow learning engagement, and ethical dilemmas related to data privacy remain key challenges. The novelty of this research lies in its integrative philosophical mapping that connects classical theories with the dynamics of 21st-century digital learning. Practically, the results of this study emphasize the importance of designing a digital education framework grounded in humanistic and reflective values. This research provides conceptual contributions for educators, policy makers, and learning designers to ensure that technology functions as a means of supporting the humanitarian goals of education, not as a determinant of the direction of education itself.